Implementation of Education Information System (SIMPATIKA) to Improve the Quality of Digital Human Resources for RA-Alfalah Teachers, Subang Regency - Salma Nurmalia; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
Education has an important role in creating quality human resources, including in the context of early childhood education at RA Al-Falah. This study aims to analyze the implementation of the Education Information System (SIMPATIKA) in improving the quality of teachers’ digital human resources. The research design uses a qualitative descriptive method to describe the phenomenon of SIMPATIKA implementation in the RA-Alfalah Educational Institution, Subang Regency. The research population consisted of school principals, teachers, and administrative staff, with a sample of six informants selected purposively. Data were collected through in-depth interviews and participatory observations and were analyzed interactively. The results show that although SIMPATIKA has the potential to improve the quality of education and administrative efficiency, a gap in teachers’ digital abilities varies. Training and technology infrastructure limitations are the main obstacles to using SIMPATIKA. Therefore, further efforts are needed in training and infrastructure improvement to maximize the benefits of this system in improving the quality of teachers’ digital human resources.